A Note on the Physical and Mechanical Properties of Robinia pseud-acacia, Fraxinus Spp. And Ailanthus Spp. from Srinagar (J & K) - Shukla, N. K.; Singh, K. R.; Singh, R. S. (Indian Forester, 1986)
Based on tests carried out on small clear specimens, the physical and mechanical properties of Robinia pseud-acacia, Fraxinus spp., and Ailanthus spp., obtained from Srinagar (J & K), are reported, discussed and compared with Robinia pseud-acacia (U.S.A.), Fraxinus excelsior (UK) and Ailanthus Integrifolia (Buxa. W.B.) and also with Tectona grandis. The safe working stresses and comparative suitability indices for various industrial and engineering uses have also been evaluated and reported. It is observed that although Robinia pseud-acacia and Fraxinus spp. From Srinagar (J & K) are slightly heavier than their U.S.A., and U.K., counterparts in strength properties the former are not consistently superior. Based on the strength propeties, the end-uses of Robinia pseud-acacia and fraxinus spp. are also suggested.